2008
DOI: 10.1071/ah080322
|View full text |Cite
|
Sign up to set email alerts
|

The Australian health care system: reform, repair or replace?

Abstract: A Festshrift gives us the opportunity to look both backwards and forwards. Ken Donald's career stretches back to his intern days in 1963 and has encompassed clinical and population health, academe, clinical settings and the bureaucracy, and playing sport at state and national levels. There has been considerable change in the health care system over the period of Ken's involvement in the sector with more change to come -where have those changes left us? This paper discusses these changes in relation to performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…Duckett 3 considers that it is extraordinary that Australia still does not have a comprehensive platform on which to build community-based health services, as the brief flirtation with a nationally mandated community health program initiated in the early 70s was undone by subsequent governments. Most organisational differences between jurisdictions are not evidence based, and having blurred the boundaries between policy direction and service delivery, most are devoting significant resources to 'crisis managing' their service systems.…”
mentioning
confidence: 99%
“…Duckett 3 considers that it is extraordinary that Australia still does not have a comprehensive platform on which to build community-based health services, as the brief flirtation with a nationally mandated community health program initiated in the early 70s was undone by subsequent governments. Most organisational differences between jurisdictions are not evidence based, and having blurred the boundaries between policy direction and service delivery, most are devoting significant resources to 'crisis managing' their service systems.…”
mentioning
confidence: 99%
“…Schlenker T found that the traditional medical providers were included in the Medicaid Waivers to help achieving the "Triple Aim" goals in the United States Texas [31]. It's suggested that the government should carry out sustainable strategic design when designing and arranging hospital investment, and allocate sufficient resources which will help to effectively address patient needs, technological changes and increased acumen [32,33]. The growth of fixed assets also has a positive impact on PTHs' revenue growth [16].…”
Section: Discussionmentioning
confidence: 99%
“…[141][142][143][144] Three aspects of economic efficiency were examined: (1) productive efficiency, analysed from econometric reports on efficiency; 10,12,13,15,22,52,145 (2) allocative efficiency measures, which, in the present study, are based on systems for priority setting for public hospital capital allocation and patient access; and (3) dynamic efficiency, assessed by examining systems for environmental sustainability, responsiveness to innovation and patient-centred care. 17 Productive efficiency was scored from three studies ranking WHO member countries for health service allocative and productive efficiency. 15,22,52 These three studies ranked 191 countries using frontier production function model and data envelope analysis, and were reviewed by an international scientific committee [146][147][148] and by the European Commission study of health system efficiency.…”
Section: Methodsmentioning
confidence: 99%
“…12 Dynamic efficiency examines how effectively capital distribution systems respond to emerging risks for public hospitals, including sustainability, patient demand, technological change and increased acuity. [17][18][19] An effective system of capital allocation for public hospitals would provide equity of access for patients, be appropriate, efficient and would fund quality services. 20 So the aim of the present study was to ask the question, is the system of capital funding for Australian hospitals effectively funding patient access to efficient public hospital care?…”
Section: Introductionmentioning
confidence: 99%